Implementation Of Risk Management In Digital-Based Training And Coaching Institutions - Musdiana Mayang Putri, Elly; Hamdi, Edi; Indradewa, Rhian; Munandar, Agus (Cattleya Darmaya Fortuna, 2024)
Risk is often associated with situations that may threaten the achievement of organisational goals and objectives. The impact of risk can be very significant, so effective risk management is very important. This study aims to analyse the implementation of risk management at PT Indotraining Multi Solusi, a digital-based training and coaching agency. Using the ISO 31000:2018 framework, this research identifies and assesses fourteen risks faced by the organisation. The research method used is qualitative with a descriptive approach to present the data in detail. The results show that by applying ISO 31000:2018, risks can be classified into four levels: low, medium, high, and extreme, which allows the company to establish appropriate risk management actions for each. This process includes risk identification, analysis, evaluation, and mitigation, as well as regular monitoring and review.